POWER AND POLITICS IN THE COMMUNITY COLLEGE (Author: Mary Lou Zoglin) - Wensley, Roland (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1977)
Mary Lou Zoglin. POWER AND POLITICS IN THE COMMUNITY COLLEGE. Palm Springs, California: ETC Publications, 1976. 166 pp. $8.95